2007
DOI: 10.1007/s11605-006-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrectomy as a Remedial Operation for Failed Fundoplication

Abstract: The decision for, and choice of, a remedial antireflux procedure after a failed fundoplication is a challenging clinical problem. Success depends upon many factors including the primary symptom responsible for failure, the severity of underlying anatomic and physiologic defects, and the number and type of previous remedial attempts. Satisfactory outcomes after reoperative fundoplication have been reported to be as low as 50%. Consequently, the ideal treatment option is not clear. The purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
3
32
1
3
Order By: Relevance
“…The newly created fundoplication may replicate the original configuration (if the previous failure was purely technical) or may involve a variation (i.e., partial fundoplication, should esophageal dysmotility coexist). Diversion of the main part of the stomach in the form of RNY reconstruction (GJ or EJ) is a recognized alternative strategy, and may be considered when a new fundoplication is not technically feasible or is expected to produce suboptimal results [15,[19][20][21]. In certain situations, esophagectomy is the only option for end-stage esophageal disease [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly created fundoplication may replicate the original configuration (if the previous failure was purely technical) or may involve a variation (i.e., partial fundoplication, should esophageal dysmotility coexist). Diversion of the main part of the stomach in the form of RNY reconstruction (GJ or EJ) is a recognized alternative strategy, and may be considered when a new fundoplication is not technically feasible or is expected to produce suboptimal results [15,[19][20][21]. In certain situations, esophagectomy is the only option for end-stage esophageal disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…Good outcomes have been reported [18][19][20][21]. Previously, we presented our initial experience with RNY reconstruction for failed fundoplication with at least 1-year follow-up [22].…”
mentioning
confidence: 97%
“…Major and/or minor complications occurred in 32% of patients without mortality in this difficult group of patients in whom reoperative fundoplication had a high likelihood of failure. A retrospective comparison between reoperative fundoplication and gastrectomy with Roux-en-Y reconstruction for failed fundoplication revealed that despite having more severe endoscopic complications of GERD and more previous fundoplications, the gastrectomy group experienced greater relief of their primary symptom [26]. In-hospital morbidity, however, was higher following gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported less than satisfactory outcomes in patients undergoing redo Collis fundoplication, especially in presence of decreased esophageal motility [18]. We have increasingly and successfully employed RNY reconstruction in a larger number of reoperative procedures [19][20][21]. This study clearly shows that patients with short esophagus and large recurrent hiatus hernia report significantly better results with RNY reconstruction compared with redo Collis gastroplasty.…”
Section: Discussionmentioning
confidence: 78%